Contingent negative variation as an evaluation indicator of neurocognitive disorder after traumatic brain injury - Ling, Xindi; Wang, Shujian; Zhang, Shengyu; Li, Wen; Zhang, Qinting; Cai, Weixiong; Li, Haozhe (Frontiers in Psychiatry, 2023)
Introduction Neurocognitive disorders are commonly observed in patients suffering from traumatic brain injury (TBI). Methods to assess neurocognitive disorders have thus drawn the general attention of the public, especially electrophysiology parameter such as contingent negative variation (CNV), which has been given more emphasis as a neurophysiological marker in event-related potentials (ERPs) for diagnosing a neurocognitive disorder and assessing its severity. The present study focused on the correlations between CNV parameters and levels of daily living activities and social function to explore the potential of CNV as an objective assessment tool. Methods Thirty-one patients with a diagnosis of neurocognitive disorder after a TBI according to ICD-10 were enrolled as the patient group, and 24 matched healthy volunteers were enrolled as the control group. The activity of daily living scale, functional activities questionnaire, social disability screening schedule, and scale of personality change following TBI were used to assess daily living activity and social function. Results The scale scores in patients were significantly higher than those in controls. Maximum amplitudes before S2 and during the post-imperative negative variation (PINV) period were also significantly higher in the patient group compared to the control group and were positively correlated with four scale scores. The duration of PINV at Fz and Cz was significantly shorter in the patient group than in the control group. The CNV return to baseline from a positive wave at electrode Fz and Cz occurred significantly earlier in the control group than in the patient group, while at Pz, the result showed the opposite. Conclusion Lower amplitudes of CNV were associated with more severe neurocognitive disorder and greater impairments in daily life abilities and social function. The duration of PINV and the latency of returning to baseline from a positive wave were correlated with the neurocognitive disorder to some extent. CNV could be used as an objective, electrophysiology-based parameter for evaluating the severity of the neurocognitive disorder and personality changes after TBI.